The Woodcraft folk song book [Bladmuziek] : with acknowledgments to authors known and unknown. (London : Woodcraft folk)
Deze brochure bevat volgende liederen
There is a Factory in the Town
Here's to the Feet
A Wayfarer's Life
The Mighty Anthem
Upidee
On Ilkley Moor baht 'at
William Brown
Shenandoah
Vagrant Song
Song of the Komsomols
England Arise
The Vow We Have Made
Song of the Outward Trail
Link Your Hands Together
Land of Freedom
Salute to Life
Wanderlied
Marianina
The Winter Has Blown Over
Faria
Farewell and a Last Goodnight
Hans Spielman
Holla Hi
Bandiera Rossa
Hallo! Hallo!
Jerusalem
Himno de Riego
Road to the Isles
Red Army March
Cwm Rhondda
Youth Song
Whirlwinds of Danger
The Internationale
Duffie, Duffie, Die
Alleluia, I'm a Bum
Waltzing Matilda
I Went to the Animals' Fair
Campfire's Burning
Over Hill and Valley
My Uncle He Sells Ole Clo'
Down at the Station
Cuckoo
We Ain't Got No Yell
The Outcry
Envoi
The Creed
Fire Lightning Ceremony
Camp Leave Take Ceremony
Indoor Leave Take Ceremony
The Campfire Carol
Engels
Bladmuziek
Keywords: liederen